Where should we camp next? Budget camping : a 50-state guide to budget-friendly campgrounds and free and low-cost outdoor activities - Puglisi, Stephanie; Puglisi, Jeremy (Sourcebooks, 2024)
"From camping and RV industry experts Stephanie and Jeremy Puglisi, WHERE SHOULD WE CAMP NEXT?: BUDGET CAMPING is your guide to planning an amazing, budget-conscious family vacation, featuring 200+ of the best and most interesting campgrounds and outdoor accommodations across the US, along with recommendations for cheap and free activities, restaurants, and more"--